2020
DOI: 10.3390/dj8030070
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Diabetes on Implant Failure and Peri-Implant Diseases: A Retrospective Study

Abstract: Diabetes is an important modifying factor of periodontitis, but its association with peri-implant diseases has not been fully explored and the existing literature reports controversial results. The aim of this retrospective study was to evaluate the influence of diabetes on peri-implantitis and implant failure. Smoking status, history of periodontal disease, presence of diabetes, diabetes type, therapy and glycaemia levels were collected in a total of 204 subjects treated with 929 implants, with a mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 21 publications
0
20
0
2
Order By: Relevance
“…In fact, the conclusions on the influence of hyperglycemia on peri-implant inflammation are still heterogeneous. 12 clinical studies (1× cross-sectional study, 5× prospective, 6× retrospective) showed no increased risk of developing peri-implantitis with manifest diabetes mellitus [ 17 , 23 , 24 , 27 , 34 , 38 41 , 44 , 46 , 77 ]. On the other hand, six studies indicated an increased risk of peri-implant inflammation, with the highest determined relative risk being given as 8.65 [ 15 , 28 , 31 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the conclusions on the influence of hyperglycemia on peri-implant inflammation are still heterogeneous. 12 clinical studies (1× cross-sectional study, 5× prospective, 6× retrospective) showed no increased risk of developing peri-implantitis with manifest diabetes mellitus [ 17 , 23 , 24 , 27 , 34 , 38 41 , 44 , 46 , 77 ]. On the other hand, six studies indicated an increased risk of peri-implant inflammation, with the highest determined relative risk being given as 8.65 [ 15 , 28 , 31 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies showed no negative influence [ 10 , 11 , 38 , 42 , 44 ], two showed a non-significant [ 29 , 36 ] and six a significantly negative influence of diabetes on implant survival [ 12 , 16 , 32 , 37 ]. For example, the study of Alberti et al [ 38 ] showed no significant difference of the implant survival after 10 years in patients with diabetes (survival rate of 96.5%) compared to patients without diabetes mellitus (survival rate of 94.8%), whereas the study of French et al [ 37 ] identified diabetes mellitus with a hazard ratio of 2.25 as a risk factor for implant failure in a multivariate analysis, implicating an over two times higher risk for failure of dental implants in patients with diabetes mellitus. In addition, eight aggregated literature references could be included on this question, whereby in seven publications, it was concluded that diabetes mellitus does not seem to have a significant influence on implant survival [ 8 , 51 , 52 , 55 58 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although emerging evidence from a number of systematic reviews and meta-analyses suggest that chronic hyperglycemia is an important risk factor for peri-implant diseases, 23,30,31 however more recent lines of evidence do not indicate any significant association between diabetes and peri-implantitis. 6,32,33 Several recent metaanalyses have shown that diabetes and in particular poor glycemic control significantly correlates with predisposition and development of peri-implantitis. 23,30,31 A recent meta-analysis found that compared to non-diabetics, twice as many patients with diabetes were at risk of periimplantitis and that higher glycemic levels (HbA1c >8%) were associated with greater prevalence of peri-implant diseases.…”
Section: Clinical Evidence For Association Of Hyperglycemia With Peri-implant Diseasementioning
confidence: 99%
“…31 However, other more recent studies have not found a similar trend between diabetes and peri-implantitis compared to metabolically healthy individuals. 6,32,33 While two studies only looked at patients with well-controlled diabetes, 6,32,33 in another independent study the male patients with poorly-controlled diabetes (HbA1c >8%) showed elevated peri-implant clinical and radiographic markers independent of periimplantitis. 6 Collectively, these studies emphasize the need for further well-controlled and long-term trials that compare patients with different glycemic profiles using consistent definitions as well as outcome indicators which can then be translated to appropriate management during implant therapy.…”
Section: Clinical Evidence For Association Of Hyperglycemia With Peri-implant Diseasementioning
confidence: 99%
“…Any disruption in this biological mechanism could have a detrimental effect on the therapy outcome [2]. Diabetes mellitus (DM), for example, can contribute to dental implant failure, as uncontrolled diabetes is associated with a tendency to develop peri-implantitis and poor osseointegration [2,6]. Studies show a strong correlation between diabetic patients and the incidence of peri-implant infection [6][7][8][9], as well as reduced osseointegration [10], as impaired glycemic control increases the release of toxic metabolites (advanced glycation end products AGEs) [11], and inflammatory cytokines interleukin 6 (IL-6) and tumor necrosis factor-α (TNF-α), which lead to a slowed healing process for dental implants, and subsequent infection and implant failure (Figure 1) [12,13].…”
Section: Introductionmentioning
confidence: 99%